State Youth Policy: to the Question of the Categorical Conceptual Framework of Research of the Problem - Pavel Alexandrovich Merkulov (Управленческое консультирование, 2018)
The article proves the need to clarify the conceptual apparatus of study of the state youth policy in Russia which according to the author will identify the individual elements of the state (effective and negative) impact on young people as a specifi c socia l group in Russian society. In this context, the author offers his own interpretation of the content of the concepts of «youth», «policy», «public policy», «state youth policy», «negative youth policy», «social class youth policy».